SERBIA ON THE INTERNATIONAL MEAT MARKET - T. Đorović, Milutin; V. Stevanović, Simo; M. Lazić, Verica (Economics of Agriculture, 2010)
The paper contains a comparative analysis of some of the most important indicators of both global and domestic meat market. Namely, the quantitative and structural differences in the production and trade of meat for observed subperiods in the last nineteen years for the world, continents and some countries were analyzed, by using the method of comparative analysis. Leading producers, international trade flows, leading exporters and importers of meat were defined, with special emphasis on the position and importance of Serbia on the world meat market. Pursuant to the above, as well as the importance of the above-mentioned product for the domestic market, ie agroindustry and the economy as a whole, the paper particularly studies balances, structure, dynamics and regional orientation of foreign trade of domestic meat and meat products. In addition, the paper points to the needs, capabilities, measures and directions of further development of domestic production and export of products analyzed.